Strategi Preventif dan Represif Satuan Polisi Pamong Praja dalam Menertibkan Pedagang Kaki Lima di Kabupaten Aceh Besar - Depita Kardiati (Jurnal Media Administrasi, 2025)
The regulation of street vendors (PKL) in Aceh Besar Regency is part of the local government's efforts to maintain public order and manage public space effectively. This study aims to analyze the preventive and repressive strategies implemented by the Municipal Police Unit in regulating street vendors. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. The findings reveal that preventive strategies are carried out through guidance activities such as socialization, counseling, and routine patrols. However, the effectiveness of these strategies remains limited due to resource constraints and low participation from the vendors. On the other hand, repressive strategies involve direct enforcement through warnings and evictions, as well as indirect enforcement through cross-sector coordination and business location relocation. Repressive measures often provoke resistance from vendors, especially since the designated relocation areas are perceived as economically unstrategic. The implications of this research highlight the importance of strengthening persuasive approaches, enhancing inter-agency coordination, and providing viable relocation sites to ensure that enforcement policies are implemented effectively, sustainably, and with public acceptance.